Altmetrics in the evaluation of scholarly impact: a systematic and critical literature review - González, Paloma; Fors, Martha; Torres, Ariel (Frontiers in Research Metrics and Analytics, 2025)
Altmetrics have emerged as a complementary tool to traditional citation-based metrics in the assessment of scholarly impact. Unlike traditional metrics that primarily capture academic citations over long periods, altmetrics reflect immediate online attention across platforms such as Twitter, blogs, news outlets, and Mendeley. This article critically examines whether altmetrics can serve as a substitute for traditional metrics by exploring their strengths, limitations, disciplinary variations, and correlation with conventional indicators. Through a review of recent empirical studies and theoretical debates, the article argues that while altmetrics offer valuable insights into social impact and engagement, they are not yet mature or standardized enough to fully replace traditional metrics. Instead, a hybrid model that integrates both systems may offer a more holistic and inclusive measure of research influence.